2020
DOI: 10.1038/s41467-020-15983-6
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibition modulates NLRP3 inflammasome activity via ketones and insulin in diabetes with cardiovascular disease

Abstract: Sodium-glucose cotransporter 2 (SGLT2) inhibitors reduce cardiovascular events in humans with type 2 diabetes (T2D); however, the underlying mechanism remains unclear. Activation of the NLR family, pyrin domain-containing 3 (NLRP3) inflammasome and subsequent interleukin (IL)-1β release induces atherosclerosis and heart failure. Here we show the effect of SGLT2 inhibitor empagliflozin on NLRP3 inflammasome activity. Patients with T2D and high cardiovascular risk receive SGLT2 inhibitor or sulfonylurea for 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
225
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(269 citation statements)
references
References 37 publications
8
225
1
1
Order By: Relevance
“…This idea is supported by the fact that ketone perfusion improves energy generation (139,140), a finding duplicated in diabetic mice treated with empagliflozin (140). Alternatively, recent work has highlighted an indirect mechanism by which SGLT2 inhibition may achieve improvements in cardiac function: Kim and colleagues demonstrated that SGLT2 inhibitors reduce activity of the NLR family, pyrin domaincontaining 3 (NLRP3) inflammasome, and that this anti-inflammatory effect may be attributable to increased ketones in concert with reduced insulin concentrations (141). As activation of the NLRP3 inflammasome worsens heart failure mortality (142), the effects of SGLT2 inhibition to suppress NLRP3 inflammasome activation secondary from reduced insulin and increased ketone concentrations would be predicted to improve outcomes.…”
Section: Sglt2 Inhibitors and Heart Failurementioning
confidence: 99%
“…This idea is supported by the fact that ketone perfusion improves energy generation (139,140), a finding duplicated in diabetic mice treated with empagliflozin (140). Alternatively, recent work has highlighted an indirect mechanism by which SGLT2 inhibition may achieve improvements in cardiac function: Kim and colleagues demonstrated that SGLT2 inhibitors reduce activity of the NLR family, pyrin domaincontaining 3 (NLRP3) inflammasome, and that this anti-inflammatory effect may be attributable to increased ketones in concert with reduced insulin concentrations (141). As activation of the NLRP3 inflammasome worsens heart failure mortality (142), the effects of SGLT2 inhibition to suppress NLRP3 inflammasome activation secondary from reduced insulin and increased ketone concentrations would be predicted to improve outcomes.…”
Section: Sglt2 Inhibitors and Heart Failurementioning
confidence: 99%
“…Our results were consistent with these studies. It was reported that SGLT2 inhibitors could inhibit the activation of NLRP3 in ammasome [17], reduce the secretion of vasoconstrictive eicosanoids and pro-in ammatory chemokines in the vasculature [15,18], playing an anti-in ammation role. A study showed that empagli ozin prevented the development of atherosclerosis and reduced in ammation and fat deposition in non-diabetic ApoE-/-mice [8].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a follow-up study by the same group showed no additional effect of BHB on inflammatory markers in in ex vivo LPS-stimulated peripheral blood mononuclear from obese subjects following an oral glucose challenge, 113 which suggests a context dependency of BHB-NLRP3 on circulating glucose or insulin concentrations. This is further underscored by a recent study demonstrating that changes in insulin and glucose concentrations modulate the effect of BHB on NLRP3 on human monocytes from diabetic patients in vitro, 114 reinforcing the complexity of this interaction, which remains to be fully defined. In addition, it is not known whether BHB affects NLRP3 activation specifically in alveolar macrophages or lung epithelial cells as it does in blood macrophages.…”
Section: Bhb Directly Inhibits Proinflammatory Nlrp3 Activationmentioning
confidence: 93%
“…184 Furthermore, both acute and chronic administration of exogenous ketones lowers glucose levels, mitigates hypoglycemic injury, and improves disease outcomes in multiple animal models of multifactorial inflammatory disease. 178,185 BHB-mediated lowering of blood glucose might have the further benefit of facilitating optimal ketone body action on inflammatory and oxidative stress pathways, which may be attenuated in the presence of high glucose 91,114 (discussed above). Together, these data suggest that exogenous ketone bodies might attenuate glycemic dysregulation and its associated adverse outcomes in patients at high mortality risk from viral infection.…”
Section: Bhb Preserves Cardiac Functionmentioning
confidence: 99%